The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m109.053348
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin Differentially Regulates the Assembly of Connexin43 and Connexin32 into Gap Junctions in Human Squamous Carcinoma Cells

Abstract: It is as yet unknown how the assembly of connexins (Cx) into gap junctions (GJ) is initiated upon cell-cell contact. We investigated whether the trafficking and assembly of Cx43 and Cx32 into GJs were contingent upon cell-cell adhesion mediated by E-cadherin. We also examined the role of the carboxyl termini of these Cxs in initiating the formation of GJs. Using cadherin and Cx-null cells, and by introducing Cx43 and Cx32, either alone or in combination with E-cadherin, our studies demonstrated that E-cadherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 67 publications
3
72
0
Order By: Relevance
“…Images of the scrape-loaded cells were captured using a CCD camera (Retiga 2000R, FAST 1394) with the aid of Volocity software (Improvision, Lexington, MA). The experiment was repeated 3 times and in each trial, 4 side by side images were captured and estimation of junction permeability was based on methods described previously where the number of fluorescent cells (containing Lucifer Yellow) were counted, excluding the cells containing dextran, which indicates the initially loaded cells (33,34). Data were analyzed statistically by analysis of variance with Tukey post hoc tests.…”
Section: Expression and Purification Of Recombinant Gst-taggedmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of the scrape-loaded cells were captured using a CCD camera (Retiga 2000R, FAST 1394) with the aid of Volocity software (Improvision, Lexington, MA). The experiment was repeated 3 times and in each trial, 4 side by side images were captured and estimation of junction permeability was based on methods described previously where the number of fluorescent cells (containing Lucifer Yellow) were counted, excluding the cells containing dextran, which indicates the initially loaded cells (33,34). Data were analyzed statistically by analysis of variance with Tukey post hoc tests.…”
Section: Expression and Purification Of Recombinant Gst-taggedmentioning
confidence: 99%
“…Scrape-loading Assay-Cells were scrape-loaded and immunostaining were performed as described in (33,34). Briefly, HeLa cells were seeded in six-well clusters at a density of 1.5 ϫ 10 6 /well and grew for 24 h prior and post-transfection.…”
Section: Expression and Purification Of Recombinant Gst-taggedmentioning
confidence: 99%
“…Antibodies and Immunostaining-Rabbit polyclonal and mouse monoclonal antibodies against Cx32 and mouse anti-␤-catenin, and rabbit anti-␤-actin have been described previously (18,19,21). We also used rabbit polyclonal antibodies raised against the carboxyl tail (Sigma; C-3470) and the cytoplasmic loop of Cx32 (Sigma, C-3595).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies we had fortuitously observed that the retrovirally expressed cytoplasmic tail-deleted Cx32 appeared to assemble into small gap junctions compared with those formed by the expression of the full-length Cx32 (18). Moreover, our previous study with cadherin-null human squamous carcinoma cells had also shown that the assembly of Cx32 into gap junctions was facilitated when cells acquired a partially polarized state and that the cytoplasmic tail of Cx32 (abbreviated as Cx32-CT) was required to initiate the formation of a gap junction plaque and/or its subsequent growth in these cells (19). These studies prompted us to explore the role of Cx32-CT in the assembly of gap junctions.…”
mentioning
confidence: 99%
“…To produce recombinant retrovirus for infection of target cells, amphotropic PTi67 cells were infected with the transiently produced recombinant retrovirus from EcoPack and selected in G418 (400 μg/ml). The recombinant retrovirus produced from the pooled polyclonal cultures of PTi67 cells was assayed for the virus titer by colony forming units as described [17][18][19][20][21][22].…”
Section: B) Prepare Recombinant Retrovirus Containing E-cadherin-camentioning
confidence: 99%